Setting Analysis of Short Story The Fall of the House of Usher - Ananda Nola Secami Pratiwi; Agung Suhadi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
“The Fall of the House of Usher" is a short story written by Edgar Allan Poe. Poe was a famous American writer, born on January 19, 1809, and died on October 7 1849 at the age of 40. He was well-known for his dark, gruesome depictions of emotionally haunted characters. The fall of the House of usher was released to the public in 1839 in Burton’s Gentleman’s Magazine. And, just like many of his works, this short story is not an exception to his collection of Gothic tales illustrating themes such as insanity, family, isolation, and supernaturals. The story tells a tale of Roderick Usher who requested the narrator to come for a visit to the old Usher's House, the narrator was a childhood friend of Roderick and has not seen him for a long time, and the Usher have grown sick and believed that his time would be soon. This study focuses on analyzing one of the key aspects in literature, which is settings. How does the setting affect the characters in the story, and does it affects the story told? The method used in this qualitative research is the descriptive method, which went through several stages including research design, data collection, and data analysis.